Efetividade do uso de mensagens de texto para a permanência e o êxito de estudantes da educação profissional e tecnológica - Temp, Haury (2022)
Access to basic education, although it does not necessarily express the recognition and reduction of social inequality, seems to be the safest and most egalitarian path in the construction of society. However, it is not always in tune with the conditions of student permanence and success in school. Therefore, the general objective of this study was to develop, implement and evaluate strategies to combat school dropout, through text messages, to contribute to the permanence and success of students in Integrated High School. The research is quantitative and applied in nature, associated with the experimental level of investigation. Initially, a scientometric study associated with the theme of school dropout in high school was carried out, rescuing the academic productions from 2005 to 2019, from the Graduate Programs of the five Federal Universities of RS. Then, an investigation was developed involving the sending of text messages built on the Theory of Self-Determination and sent to students of the Integrated High School of IFFar, through the WhatsApp application. The first intervention took place during the second semester of 2019 and lasted 14 weeks, in which 99 students with low academic performance participated. Four groups were created: the control group, which did not receive the messages, and the groups that received the messages with different weekly frequencies (every 15 days; one message/week or three messages/week). The second intervention took place for eight weeks, in the second half of 2020, in the midst of the COVID-19 Pandemic, characterized by remote teaching. In this study, 560 students from three years of high school participated, in which three messages were sent per week. Regarding the scientometric study, 15 productions related to school dropout in high school were found, making it possible to identify that the main causes for dropping out of school are low interest and the study/work relationship; the possible alternatives to reduce dropout are related to greater participation of the school community, the construction of pedagogical projects and curricular adequacy. Regarding the effect of the use of text messages on students' school performance, during face-to-face teaching, based on the status at the end of the school year, grade and number of failures in subjects, it was possible to prove that the use of text messages with motivation was relevant to improve students' school performance, especially those who received three messages per week. The results of the intervention, during remote teaching, showed that the use of text messages provided greater acceptance for students and an increase in their state of motivation. Similarly, it was possible to identify the development of basic psychological needs configured by the dimensions of autonomy, competence and belonging in students, after receiving the messages. Thus, it is concluded that the use of motivational messages via smartphone is an important alternative to prevent retention and dropout of students from Integrated High School, based on increased motivation, performance and engagement of students with the feasibility of inclusion in the action plan of institutional permanence and success programs.